PEMANFAATAN MEDIA E-LEARNING EDLINK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA - Valleri Rehan Prima Vincinzo; Dyah Astriani (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
The purpose of this research was to determine the improvement of critical thinking skills and student responses to the use Edlink e-learning media on the human digestive system materials. This research uses a pre experimental design method with a One Group Pretest-Posttest. The research was conducted at SMP Negeri 46 Surabaya involving students in class VIII-A (experimental class) and class VIII-B (replication class). The results showed that the use of Edlink e-learning media could improve students critical thinking skills. The increase in the percentage of students critical thinking in class VIII-A in the medium category is 62.07% and the high category is 37.93%. Class VIII-B experienced an increase in the percentage of critical thinking in the low category of 3.35%, medium category 62.07%, and high category 34.48%. The results of student responses gave a positive response. Students feel happy, enthusiastic, and interested in taking part in learning activities using the Edlink e-learning media. Thus, the use of Edlink e-learning media makes online learning more meaningful so that students critical thinking skills increase.